On the design and manufacturing of topologically optimized wings. Issue 4 (25th October 2021) - Proença, Tiago; Afonso, Frederico; Lau, Fernando; Policarpo, Hugo; Lourenço, João
Abstract : Purpose: The purpose of this paper is to evaluate the impact of different Additive Manufacturing (AM) orientations on the structural behavior of topologically optimized wings for Unmanned Aerial Systems (UAS), which might enable lightweight and low cost, yet complex, wing structural designs. Design/methodology/approach: Based on an aerodynamic load, a two dimensional NACA0012 airfoil is topologically optimized considering PolyLatic Acid (PLA), several volume fractions and different manufacturing orientations. Then, the resulting topologies are post-processed to allow for manufacturing and extrude to three dimensional wing geometries with constant cross-sections. These wings are then manufactured using Fusion Deposition Modeling (FDM) technology and their dynamic structural behavior analyzed by means of Experimental Modal Analysis (EMA) in the linear elastic region. Findings: Volume fraction increase is observed to improve the structural performance without increasing the manufacturing time. Despite manufacturing the wing from the leading edge to the trailing edge can reduce manufacturing time using FDM technology, it is found to be more difficult to build. Originality/value: This research is a contribution toward the design and built of lightweight and low cost wings for UAS.